Impacts of Daily Habits, Health Status, and Health Promoting Behavior on Prevalence of Irritable Bowel Syndrome among Female Adolescents - Hye Young Kim (Korean Society of Women Health Nursing, 2016)
PURPOSE: This study was to investigate impacts of daily habits, health status and health promoting behavior on prevalence of irritable bowel syndrome (IBS) among female high school students. METHODS: The survey was conducted from 526 female students in high school. Rome III criteria was used to diagnose IBS. Data of daily habits, health status, and health promoting behavior were collected through self-administered structured questionnaires. RESULTS: The prevalence of IBS was 25.7%. Compared to the non-IBS, the IBS group scored significantly lower in exercise time, sleeping time, four dimensions of health status (physical, emotional, social, spiritual health) and management of relationship and stress in health promoting behavior. Risk factors influencing IBS were exercise time, physical health and emotional health status. CONCLUSION: The results of this study suggest that nursing interventions and education programs are important to be developed, while considering exercise, health status and health promoting behaviors for female adolescents in order to manage their IBS.